Conversational implicature forms of Banyumasan humorous utterances on YouTube - Wijiasih Eka Pertiwi; Dadang Sudana; Andika Dutha Bachari (Journal of Research on English and Language Learning (J-REaLL), 2023)
This study focuses on conversational implicatures in humorous utterances. In pragmatics, implicature analysis is used to reveal the additional meaning or implied meaning of the speech conveyed by the speaker. An implicature can occur because of a violation of the principle of conversation. Conversational implicature (especially) only appears in the context of certain utterances and has an implied meaning. An utterance in a conversation can imply a pragmatic function implicitly or imply some meaning indirectly through language. This study aims to describe the implicature forms of Banyumasan humorous utterances on YouTube. This study was analyzed using Searle’s (1969) speech acts theory and Grice’s (1975) theory of conversational implicature. The method in this research was descriptive qualitative. Based on the results of the analysis found in Banyumasan humorous speech, there are assertive, directive, expressive, and commissive implicature forms.